2014
DOI: 10.1200/jco.2014.32.3_suppl.lba7
|View full text |Cite
|
Sign up to set email alerts
|

RAINBOW: A global, phase III, randomized, double-blind study of ramucirumab plus paclitaxel versus placebo plus paclitaxel in the treatment of metastatic gastroesophageal junction (GEJ) and gastric adenocarcinoma following disease progression on first-line platinum- and fluoropyrimidine-containing combination therapy rainbow IMCL CP12-0922 (I4T-IE-JVBE).

Abstract: LBA7 Background: RAM is a human IgG1 monoclonal antibody VEGF-receptor 2 antagonist. We conducted a global, placebo-controlled, double-blind, phase III trial to evaluate the efficacy and safety of PTX +/- RAM in patients with metastatic GEJ or gastric adenocarcinoma who had disease progression on or within 4 months after first-line platinum- and fluoropyrimidine-based combination therapy. Methods: Pts received RAM (8 mg/kg IV q2w) or placebo (PL) plus PTX (80 mg/m2 d1, 8, 15 of a 4 week cycle) until disease p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
45
0
2

Year Published

2014
2014
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 0 publications
1
45
0
2
Order By: Relevance
“…3 Thus, after a decade of repeated failures of most targeted agents, except HER2, in showing survival benefits in gastric cancer, these positive trial results have opened a new era for exploring targeted agents for the treatment of gastric cancer. 4,5 Fibroblast growth factor receptors (FGFRs) are transmembrane tyrosine kinase receptors, and binding of ligands to FGFRs leads to activation of the downstream PI3K-AKT and MAPK-ERK pathways.…”
mentioning
confidence: 99%
“…3 Thus, after a decade of repeated failures of most targeted agents, except HER2, in showing survival benefits in gastric cancer, these positive trial results have opened a new era for exploring targeted agents for the treatment of gastric cancer. 4,5 Fibroblast growth factor receptors (FGFRs) are transmembrane tyrosine kinase receptors, and binding of ligands to FGFRs leads to activation of the downstream PI3K-AKT and MAPK-ERK pathways.…”
mentioning
confidence: 99%
“…For anti-angiogenic agents, this limitation is often due to the lack of validated predictive biomarkers. 26,31,[33][34][35]37,39,52,[60][61][62][63][64] In other cases, in particular for the anti-EGFR agents, even if the prominent role of RAS/RAF mutational status in colon cancer has been widely recognized so far, it is conceivable that this information was unknown at the time of studies design. 27,30,51,[65][66][67] Therefore it is highlighted the need of new trials designed to investigate the relevance of RAS mutation in predicting response to anti-EGFR mAbs, in aGC.…”
Section: Discussionmentioning
confidence: 99%
“…[22][23][24] Recently, RCTs investigated the efficacy of the targeted therapy alone or in combination with chemotherapy, but results were mostly unsatisfactory. [25][26][27][28][29][30][31][32][33][34][35][36][37][38] While several RCTs demonstrated an improvement in terms of response rate (RR), and progression free survival (PFS) only one study reported a significant increase in terms of OS in a selected subgroup of patients in front-line treatment. 25 In that trial, patients were selected according to HER2 status (resulted to be overexpressed in 16-34% of patients with intestinal type and 2-7% of diffuse aGC), and subsequently treated with trastuzumab plus standard chemotherapy with a significant 2.7 months advantage in OS.…”
Section: Conventional Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, ramucirumab, a fully human IgG1 monoclonal antibody to VEGFR-2, has demonstrated single-agent activity in the second-line setting, both alone and in combination with weekly paclitaxel therapy, and two large randomised phase III trials have reported survival benefits [31,32]. Efforts to improve outcomes in the first-line setting by combining ramucirumab with combination chemotherapy (5-fluorouracil and oxaliplatin) have been less successful, with a recently reported randomised phase II trial failing to demonstrate an improvement in median progression-free survival from the addition of ramucirumab therapy [33].…”
mentioning
confidence: 99%